Climatology of Upper Air Temperature Over the Mediterranean. Trends and Variability - Philandras, C. M.; Kapsomenakis, J.; Nastos, P. T.; Repapis, C; Zerefos, C. S. (PERSPECTIVES ON ATMOSPHERIC SCIENCES, 2016)
{This study shed light on the long term air temperature changes in the troposphere over the Mediterranean. For this purpose, we utilized the radiosonde datasets for the barometric levels at 850, 700, 500, 300, 200, 150, and 100 hPa from seventeen meteorological stations within the Mediterranean, for the period 1965-2015. Besides, the gridded reanalysis products of upper air temperature for the respective barometric pressure levels from the European Centre for Medium-Range Weather Forecasts (ECMWF, ERA-Interim) and the National Center for Environmental Prediction-National Center for Atmospheric Research (NCEPNCAR) were used and compared to stations' datasets. We analyzed the trends and variability of upper air temperature on seasonal and annual basis. The impact of atmospheric circulation, by means of specific climatic indices such as Mediterranean Oscillation Index (MOI), North Sea Caspian Pattern Index (NCPI) and North Atlantic Oscillation Index (NAOI), was also examined. The results of our analysis indicate the anthropogenic forcing to climate variability, especially in lower/middle troposphere against upper troposphere over the Mediterranean.}